1996
DOI: 10.1210/jcem.81.8.8768883
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian steroid regulation of vascular endothelial growth factor in the human endometrium: implications for angiogenesis during the menstrual cycle and in the pathogenesis of endometriosis.

Abstract: The human endometrium undergoes a complex process of vascular and glandular proliferation, differentiation, and regeneration with each menstrual cycle in preparation for implantation. Vascular endothelial growth factor (VEGF) is an endothelial cell-specific angiogenic protein that appears to play an important role in both physiological and pathological neovascularization. To investigate whether VEGF may regulate human endometrial angiogenesis, we examined VEGF messenger ribonucleic acid (mRNA) and protein thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
212
1
12

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(255 citation statements)
references
References 21 publications
27
212
1
12
Order By: Relevance
“…5). This level of induction is comparable to the documented induction of VEGF mRNA by estradiol in primary human endometrial cells (9). A series of deletion constructs prepared by digestion with restriction enzymes were transiently transfected into Ishikawa cells in the presence of the ER␣ expression vector.…”
Section: Vegf Gene Transcriptional Up-regulation By 17␤-estradiol Is Eresupporting
confidence: 67%
See 2 more Smart Citations
“…5). This level of induction is comparable to the documented induction of VEGF mRNA by estradiol in primary human endometrial cells (9). A series of deletion constructs prepared by digestion with restriction enzymes were transiently transfected into Ishikawa cells in the presence of the ER␣ expression vector.…”
Section: Vegf Gene Transcriptional Up-regulation By 17␤-estradiol Is Eresupporting
confidence: 67%
“…Estradiol and VEGF, respectively, are the hypothetical mediators that we chose to investigate. In the human endometrium, VEGF mRNA begins to increase in the midproliferative phase and reaches a maximum in late proliferative and secretory endometrium (9). Beginning in the late proliferative phase, under the influence of ovarian estradiol production, a complex subepithelial capillary plexus develops in the cycling endometrium (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the role of vascular endothelial growth factor (VEGF) expression in the vascularization of the endometrium. Low VEGF results in poor development which in turn decreases the blood flow to the endometrium [22][23][24][25][26]. Miwa et al [27] showed that thin endometrium is characterized by poor growth of the glandular epithelium, high uterine blood flow impedance of radial artery, decreased VEGF and poor vascular development.…”
Section: Discussionmentioning
confidence: 99%
“…Die indirekte angiogene Wirkung von Östrogenen manifestiert sich in ihrer Wirkung, die Expression von angiogenen Faktoren zu steuern. So konnte gezeigt werden, daß Östrogene die Expression des bedeutsamsten angiogenen Wachstumsfaktors VEGF in einer Reihe von Zellen (Endometriumzellen, Makrophagen) deutlich stimulieren können [32,52].…”
Section: Angiogene Wirkungen Von öStrogenenunclassified